EXPONENCIAL DECAY FOR THE SEMILINEAR WAVE EQUATION WITH POTENTIAL AND LOCAL DISTRIBUTED DAMIPING - Pérez Salvatierra, Alfonso (2004)
In this notes we shall study the exponential decay for the semilinear wave equation with potential and locally distributed damping, using the unique continuation principle, result studied by Ruíz [9] applied to problems of asymptotic behavior by Zuazua [10].